Efficacy of Precut Endoscopic Mucosal Resection for Treatment of Rectal Neuroendocrine Tumors - Hoonsub So; Su Hyun Yoo; Seungbong Han; Gwang-un Kim; Myeongsook Seo; Sung Wook Hwang; Dong-Hoon Yang; Jeong-Sik Byeon (Korean Society of Gastrointestinal Endoscopy, 2017)
Background/Aims Endoscopic resection is the first-line treatment for rectal neuroendocrine tumors (NETs) measuring <1 cm and those between 1 and 2 cm in size. However, conventional endoscopic resection cannot achieve complete resection in all cases. We aimed to analyze clinical outcomes of precut endoscopic mucosal resection (EMR-P) used for the management of rectal NET. Methods EMR-P was used to treat rectal NET in 72 patients at a single tertiary center between 2011 and 2015. Both, circumferential precutting and EMR were performed with the same snare device in all patients. Demographics, procedural details, and histopathological features were reviewed for all cases. Results Mean size of the tumor measured endoscopically was 6.8±2.8 mm. En bloc and complete resection was achieved in 71 (98.6%) and 67 patients (93.1%), respectively. The mean time required for resection was 9.0±5.6 min. Immediate and delayed bleeding developed in six (8.3%) and 4 patients (5.6%), respectively. Immediate bleeding observed during EMR-P was associated with the risk of delayed bleeding. Conclusions Both, the en bloc and complete resection rates of EMR-P in the treatment of rectal NETs using the same snare for precutting and EMR were noted to be high. The procedure was short and safe. EMR-P may be a good treatment choice for the management of rectal NETs.